PENGARUH DIGITAL MARKETING DAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS PELANGGAN (STUDI PADA PARTNER PERCETAKAN) - Dzulfikri Azis Muthalib (JIMR : Journal Of International Multidisciplinary Research, 2026)
This study aims to examine the effect of digital marketing and customer relationship management (CRM) on the loyalty of business partners of a printing company (percetakan) in Kendari. This research employs a quantitative approach with a causal research design. Data were collected through a questionnaire distributed to 85 active printing partners selected using purposive sampling, with criteria of having partnered with the company for at least six months and having placed a minimum of three printing orders during that period. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that digital marketing has a positive and significant effect on partner loyalty. Customer relationship management also has a positive and significant effect on partner loyalty, with a more dominant influence than digital marketing. Simultaneously, digital marketing and CRM explain a substantial proportion of the variance in partner loyalty. These findings suggest that printing business partners evaluate their relationship with the company holistically, weighing both digital engagement and the quality of relational management they receive.